Dylan and Cohen poets of rock and roll - Boucher, David 1951- (Bloomsbury, 2004)
Bob Dylan and Leonard Cohen are widely acknowledged as the great pop poets of the 1960s. This text provides a political, psychological and artistic profile of two iconic writers and performers.
Includes bibliographical references (p. )
Keywords: Cohen, Leonard <1934->; Dylan, Bob <1941->; Cohen, Leonard -- 1934-2016; Dylan, Bob -- 1941-; Geschichte 1900-2000; Musiciens rock - États-Unis - Biographies; Musique et littérature - Histoire - 20e siècle; Poètes canadiens - 20e siècle - Biographies; Geschichte; Music and literature -- History -- 20th century; Poets, Canadian -- 20th century -- Biography; Rock musicians -- United States -- Biography; USA; Biografie